2009
DOI: 10.1159/000200929
|View full text |Cite
|
Sign up to set email alerts
|

Extracranial Stereotactic Radiotherapy: Preliminary Results with the CyberKnife®

Abstract: In the field of radiation oncology, equipment for fractionated radiotherapy and single-dose radiosurgery has become increasingly accurate, together with the introduction of robotized treatments. A robot is a device that can be programmed to carry out accurate, repeated and ad-justed tasks in a given environment. Treatment of extracranial lesions involves taking into account organ mobility (tumor and healthy tissue) whilst retaining the ability to stereotactically locate the target. New imaging techniques (sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 35 publications
0
11
0
7
Order By: Relevance
“…8,9,16 CyberKnife delivers extracranial stereotactic radiotherapy with millimetric precision, leading to disease control and toxicity profiles that are equal to or better than those of other available therapies. 10 Although areas irradiated using conventional radiotherapy show local recurrence, in the present case, AS could be controlled for 1 year using CyberKnife, even the remote metastatic lesions. Our present case suggested that CyberKnife is one of the optimal tools for the local control of AS.…”
Section: Discussionmentioning
confidence: 55%
“…8,9,16 CyberKnife delivers extracranial stereotactic radiotherapy with millimetric precision, leading to disease control and toxicity profiles that are equal to or better than those of other available therapies. 10 Although areas irradiated using conventional radiotherapy show local recurrence, in the present case, AS could be controlled for 1 year using CyberKnife, even the remote metastatic lesions. Our present case suggested that CyberKnife is one of the optimal tools for the local control of AS.…”
Section: Discussionmentioning
confidence: 55%
“…Reviews mainly agree on the advantages of the system, such as the frameless usage, accuracy in less than 1mm, image fusion capability with multiple modalities, real time tumor tracking, and treatment possibility with linear accelerator [3,[6][7]. The majority of clinical trials using CK are mainly focused on intracranial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Le système orthogonal permet de suivre la cible en temps réel grâce à des marqueurs implantés de type fiduciaire ou par corrélation osseuse. La précision inframillimétrique de l'irradiation est obtenue grâce aux collimateurs, au positionnement tridimensionnel ainsi qu'au repositionnement en temps réel [13,14]. Les indications dans les métastases osseuses du cancer du sein sont nombreuses, notamment au niveau du rachis [9].…”
Section: Apport Du Cyberknife ®unclassified